KAJIAN STRATEGIS TATA KELOLA KOLABORATIF PASAR TRADISIONAL DATAH MANUAH KOTA PALANGKA RAYA - Satia, Muhammad Riban; Selawaty, Desy; Riyanti, Nova; Rahman, Sirajul (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
The Palangka Raya City Government is experiencing problems in managing traditional markets. The Palangka Raya City Government submitted a proposal to the central government through the ministry to revitalize the Datah Manuah traditional market. Traditional market revitalization has been carried out repeatedly, but unfortunately, its existence after revitalization is not as significant as expected. This research aims to analyze government policies in the revitalization of traditional markets and examine the governance strategy for the Datah Manuah market in Palangka Raya City. This research uses a research design that will be used, namely a qualitative design. Data collection uses observation, in-depth interviews, and documentation studies. The stages of data analysis were carried out by data reduction, data interpretation, and concluding/data verification. Apart from that, FGD activities were also carried out to strengthen data analysis. The results of this research show that Collaborative Governance of the Datah Manuah Market in Palangka Raya City has been conceptually carried out involving three actors, including the city government, the private sector, and the community. However, the existing involvement is not yet strategic, considering that in recent years there has been no significant increase in datah Manuah market development. In fact, there tends to be a decline in economic growth that occurs in these traditional markets. The conclusions also contain practical and theoretical implications to serve as a basis for other researchers to study in more depth regarding good collaborative management strategies.